Development of a Microstrip Ring Resonator for Measurement of Moisture in Oil Palm Fruits and Seeds - Ali Abrass, Hameda (2007)
The conventional oven method for the determination of moisture content in oil palm fruits and seeds is too laborious and time-consuming. An alternative method is to use microwave method, which is widely known to be accurate and rapid. However not all microwave techniques are suitable for single fruit or seed measurements due to small sample size. This thesis describes the development of a microstrip ring resonator to determine moisture content in oil palm fruits and seeds. The measurement system consists of the mirostrip resonator as sensor and PC-controlled vector network analyzer (VNA). This measurement software has been developed to control and acquire data from the VNA using Agilent Visual Engineering Environment Software. The microstrip ring resonator operates between 2.2 GHz and 3 GHz. The microstrip ring resonator operates at a low microwave frequency to allow wider electromagnetic field interaction between the resonator and the fruit sample. A theoretical analysis has been carried out to establish the optimum operating frequency based on the relationship between the admittance and frequency of the microstrip ring. The propagation of electromagnetic wave is assumed to be transverse electromagnetic (TEM) mode. The actual moisture content was found by standard oven drying method. A calibration equation relating the measured and predicted values for both magnitudes (dB) of S11 and S21 was established. The equation was found to be accurate within 1.55% and 3.35% for the magnitude (dB) of S11 and S21, respectively in the fruit samples. Similarly, the equation was found to be accurate within 2.89% and 3.38% for magnitude (dB) of S11 and S21, respectively, in the seed samples. A calibration equation which relates the measured and predicted moisture content was also been established. The equation was found to be accurate within ± 2.7% for S11 and ± 2.9% for S21 for the fruit samples, whilst within ± 3% for S11 and ± 3.2% for S21 for the seed samples. The accuracy of this technique in determining the moisture content was tested on more than 160 different fruit and seed samples.